Relationship between Characteristics of Breastfeeding Mother with Exclusive Breastfeeding in Leran Village Kalitidu District Bojonegoro Regency - Ana Istighfarisma; Shintia Yunita Arini; Anggara Widyartanto; Banatul Lariza; Hidayatul Rulling Amanda Sari (Media Gizi Kesmas, 2021)
ABSTRACTBackground: Breast milk (ASI) is a liquid created specifically that comes directly from the breast of a mother for babies and is the best food for babies especially aged 0-6 months. Factors that influence exclusive breastfeeding to mothers include maternal sociodemographic factors, pre/post natal factors, and psychosocial factors. Bojonegoro Regency is one of the regions in Indonesia that has quite good exclusive breastfeeding coverage in 2018 to reach 87%. However, there are still a number of sub-districts and public health service in Bojonegoro that have not been able to reach the target of breastfeeding coverage by the Ministry of Health in 2015, one of them is Leran Village, Kalitidu District, Bojonegoro Regency.Objective: This study determined the relation between characteristics of breastfeeding mothers consisting of age, education, occupation, and parity with exclusive breastfeeding in Leran Village, Kalitidu District, Bojonegoro Regency.Methods: The method is observational type and analytic descriptive which uses cross sectional approach. Variables studies had a relationship with exclusive breastfeeding if p < 0,05.Result: As many as 56% of mothers do not give exclusive breastfeeding. Most of the mothers who do not provide exclusive breastfeeding have low education (78,6%), aged 36-45 years (57,1%), are housewives (64,3%), and multiparous (50%). Statistical analysis showed no relation to the variables age (p=0,099), occupation (p=0,165), parity (p=0,208) with exclusive breastfeeding. While the education (p=0,003) have a relation with exclusive breastfeeding.Conclusion: The conclusion of this study is that there is no relation between age, occupation, and parity of mothers with exclusive breastfeeding. However, there is a relation between mother's education and exclusive breastfeedingKeywords: exclusive breastfeeding, mother's age, mother's education, mother's occupation, parity